Information provision improvement with a geofencing event-bases system - Monfort Muriach, Aida (2015)
Nowadays there is a big percentage of the population, specially young users, which are smartphone users and there is a lot of information to be provided within the applications, information provision should be done carefully and should be accurate, otherwise an overload of information will be produced, and the user will discard the app which is providing the information. Mobile devices are becoming smarter and provide many ways to filter information. However, there are alternatives to improve information provision from the side of the application. Some examples are, taking into account the local time, considering the battery level before doing an action and checking the user location to send personalized information attached to that location. SmartCampus and SmartCities are becoming a reality and they have more and more data integrated every day. With all this amount of data it is crucial to decide when and where is the user going to receive a notification with new information. Geofencing is a technique which allows applications to deliver information in a more useful way, in the right time and in the right place. It consists of geofences, physical regions delimited by boundaries, and devices that are eligible to receive the information assigned to the geofence. When devices cross one of these geofences an alert is pushed to the mobile device with the information.